Effects of changes in earned income tax credit: Time-series analyses of Washington DC. (April 2019) - Wagenaar, Alexander C.; Livingston, Melvin D.; Markowitz, Sara; Komro, Kelli A.
Abstract: Poverty has numerous deleterious effects on health, and the Earned Income Tax Credit (EITC) is the major policy tool used to alleviate poverty in the U.S. We evaluate effects of four distinct changes in earned income tax credit law in Washington, DC on maternal behaviors and infant outcomes. An interrupted time-series design was used with 312 monthly measures from 1990 through 2015 analyzed in 2018 (total n = 225, 933 births). States with no EITC were included as the comparison group; analyses involved ARIMA modeling. Outcomes were derived from birth certificates, and included percent of live births below 2500 g, mean birth weight, mean gestation weeks, first trimester prenatal care, and maternal smoking during pregnancy. We found a pattern of significant improvements across all three infant outcome measures, with the size of the effect estimate monotonically matching the magnitude of the tax credit—ranging from a 1.9 (-2.9, -0.9) reduction in rate per 100 births of low birth weight for the smaller 10% credit, to a 4.7 (-5.4, -4.0) reduction with the 40% credit. Results for maternal smoking and prenatal care were mixed. Results suggest that earned income tax credit policies improve birth outcomes; mechanisms for this effect deserve further study.